Alterações na parede celular e no metabolismo energético de Saccharomyces cerevisiae submetida à alta pressão hidrostática - Carneiro, Tárcio (2018)
Yeasts are one of the most important organisms in the processes of industrial biotechnology. Its great fermentative capacity and considered as a genetically safe organism, made this organism one of the first to be domesticated by the human being. Among its applications are not only its products generated from the fermentation, but also its cell itself, which moves a market ranging from organic yeast to yeast paste for human consumption. Understanding not only the fermentative process, but also the respiratory process are necessary. The production processes in which the yeasts are employed expose them to abiotic stresses of different types, such as temperature variation, pH, salinity and others. High hydrostatic pressure is now an important methodology in the study of its effects on the cells of Saccharomyces cerevisiae, acting as a model of stress. The understanding of this phenomenon on cells has helped not only to understand the processes of response to stress, but also its use as an important tool in industrial application. Atomic force microscopy, high performance liquid chromatography (HPLC) and microarray data were used to characterize the effects of high hydrostatic pressure on the cell wall of Saccharomyces cerevisiae and its energy metabolism. For the production of the experiments, BT0510 cells were submitted to high hydrostatic pressure (50 to 200 MPa) for 30 minutes and then analyzed by atomic force microscopy and in another experiment the cells were subjected to a pressure of 50MPa for 30 minutes and facing to agitation. The results showed the appearance of resistance bands in the cell wall at pressures of 100, 150 and 200 MPa, indicating possible fracture points, which leads to lesions that compromise its viability. At pressures of 50MPa the variation of the resistance of the cell wall resembles the control, which shows that this pressure is of sublethal character, not interfering so expressively in the cellular mortality. The response to 50 MPa treatment was then analyzed in the long term by HPLC, with collection points at 1, 2, 3, 4, 12, 36 and 60 hours after application of pressure. The results show high affinity with microarray generated data, where the cells increase the rate of glucose consumption in the fermentative phase (1 to 12 hours) as well as higher ethanol production. The cells also showed a greater efficiency in the ethanol metabolism which generated an increase in the cell mass in the cells treated with pressure. It was demonstrated that high hydrostatic 6 pressure has industrial application in cellular mass acquisition processes as in the production of biological yeast, thus showing the biotechnological capacity of the use of this stress mechanism and generating the deposit of the patent "Process for the increase of cellular mass in yeasts using high hydrostatic pressures ".